2016
DOI: 10.1136/jclinpath-2016-203907
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of acute intermittent porphyria in a cohort of South African patients and kinetic analysis of two expressed mutants

Abstract: This study comprises the most comprehensive characterisation of gene mutations in patients with AIP in South Africa. The biochemical characterisation of expressed mutants reveals insight into the mechanism of catalytic activity loss, which may inspire investigation into individualised therapy based on the molecular lesion identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Currently, some mutations have been tested for enzyme activity analysis in vitro, The enzyme activity of homozygotes of most mutations in vitro expressed <5%, which is consistent with the decrease of half the residual enzyme activity of heterozygotes in vivo. [9,10,20,21,23,24,32–38] However, some of the homozygotes in vitro expressed the enzyme activity close to normal, ex. c.532 G>A and c.176 C>T, the residual enzyme activity of the homozygote reached 81% in vitro, while the heterozygote residual enzyme activity was 40% in vivo, [10,34] the reasons for this phenomenon need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, some mutations have been tested for enzyme activity analysis in vitro, The enzyme activity of homozygotes of most mutations in vitro expressed <5%, which is consistent with the decrease of half the residual enzyme activity of heterozygotes in vivo. [9,10,20,21,23,24,32–38] However, some of the homozygotes in vitro expressed the enzyme activity close to normal, ex. c.532 G>A and c.176 C>T, the residual enzyme activity of the homozygote reached 81% in vitro, while the heterozygote residual enzyme activity was 40% in vivo, [10,34] the reasons for this phenomenon need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…(8) Although only few genetic studies in patients with VP or AIP have been performed in South Africa, these have identified novel mutations amongst black individuals and provide evidence for heterogeneity of molecular abnormalities in different populations. (7,26) Robreau-Fraolini et al (2000) performed the first porphobilinogen deaminase gene study within a black population, demonstrating that the spectrum of mutations differ compared to those found in white counterparts. (27) They identified four novel mutations and further discovered that certain single nucleotide polymorphisms existed only in black individuals and not in whites.…”
Section: Discussionmentioning
confidence: 99%
“…The true prevalence thereof is difficult to quantify as the clinical penetrance is low. (1,6,7) AIP is the most identified porphyria worldwide. (1,3,8,9) In South Africa, VP is the most common porphyria due to the founder R59W mutation introduced by a Dutch settler in 1688.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is a lack of epidemiological data on AIP worldwide, but Europe performed large scale prospective study to investigate the incidence of porphyrias ( Elder et al, 2013 ). And multiple countries such as South Africa ( Fortgens et al, 2017 ), the United States ( Bonkovsky et al, 2014 ), Argentina ( Cerbino et al, 2015 ), Colombia ( Jaramillo-Calle and Aguirre Acevedo, 2019 ), and Russia ( Goncharova et al, 2019 ) have reported cohort studies on AIP. And with the development of sequencing technology, more and more AIP patients have been reported in China.…”
Section: Introductionmentioning
confidence: 99%